Development of Web-Based Media Integrated with 3D Models for Training Information Literacy - Triantono, Rishal Rahmad; Rivaldi, Muhammad; Norra, Bunga Ihda; Rasyida, Nisa (Biosfer: Jurnal Tadris Biologi, 2024)
One aspect that also influences learning is information literacy, which is one of the knowledge and skills of the 21st century. Based on the results of the needs analysis of XI MIPA students at Senor High School, the average score for information literacy skills only reached 33.74%. Apart from that, the implementation of information literacy is only limited to finding and using information obtained on the internet to complete assignments given by the teacher. This research aims to develop a web-based learning media integrated 3D models to train the information literacy skills called Biology Insight. The type of research used is Research and Development (R&D), through the ADDIE development model. The data analysis technique used is descriptive analysis. The research results show that the Biology Insight web is declared very valid and suitable for use in the learning process of class XI MIPA students. This is proven by the validation results of media experts (88%) and material experts (97.5%), readability vi tests through Biology teacher responses (98.8%) and student responses on a small scale (87%).ABSTRAK: Salah satu aspek yang turut memengaruhi pembelajaran yaitu literasi informasi yang merupakan salah satu pengetahuan dan keterampilan abad ke-21. Berdasarkan hasil analisis kebutuhan terhadap siswa XI MIPA Sekolah Menegah Atas, nilai rata-rata keterampilan literasi informasi hanya mencapai 33,74%. Selain itu, implementasi literasi informasi hanya sebatas menemukan dan menggunakan informasi yang didapatkan diinternet. Penelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis web terintegrasi model 3D untuk melatih kemampuan literasi informasi yang dinamakan Biology Insight. Jenis penelitian yang digunakan yaitu Research and Development (R&D), melalui model pengembangan ADDIE. Teknik analisis data yang digunakan yaitu analisis deskriptif. Hasil penelitian menunjukkan bahwa web Biology Insight dinyatakan sangat valid dan layak untuk digunakan dalam proses pembelajaran siswa kelas XI MIPA. Hal ini dibuktikan dari hasil validasi ahli media (88%) dan ahli materi (97,5%), uji vi keterbacaan melalui respon guru Biologi (98,8%) dan respon siswa dalam skala kecil (87%).